Maternal Knowledge and Confidence Influence Exclusive Breastfeeding: A Study of Mothers of Toddlers in Teluk Kapuas Village, Kubu Raya, West Kalimantan, Indonesia: Pengetahuan dan Kepercayaan Diri Ibu Mempengaruhi Pemberian ASI Eksklusif: Studi Ibu Balita Desa Teluk Kapuas, Kubu Raya, Kalimantan Barat, Indonesia - Desi Wahyuni; Ayu Rizky; Marlenywati (Muhammadiyah Institute of Technology and Health, West Kalimantan (ITEKES Muhammadiyah Kalimantan Barat), 2024)
Background: One of the efforts to increase quality resources is by giving milk, especially exclusive breastfeeding. In 2019, in Teluk Kapuas Village, Kubu Raya Regency, West Kalimantan Province, the number of exclusively breastfed toddlers was 41.3%, which is very far from achieving the national target of 80%. Objective: The purpose of this study was to determine the factors of exclusive breastfeeding in mothers who have toddlers 6-24 months in Teluk Kapuas Village, Kubu Raya Regency, West Kalimantan Province. Methods: This type of research used Observational analytic with Cross Sectional approach. The sample in this study amounted to 46 respondents taken by simple random sampling. Data analysis in this study with univariate analysis and bivariate analysis using Chi-square test Results: The results showed that the related variables were maternal knowledge with a value of (P = 0.031), maternal self-confidence with a value of (P = 0.000). While the unrelated variables are the support of the closest person with a value of (P = 0.632), the mother's attitude with a value of (P = 0.454), the mother's work status with a value of (P = 0.756), the support of health workers with a value of (P = 1.000). Conclusion: It is important to provide intensive educational programs for mothers of toddlers about the importance of exclusive breastfeeding, with a focus on increasing maternal knowledge and confidence to increase exclusive breastfeeding.